Awareness and Self-Reported Health Hazards of Electromagnetic Waves from Mobile Phone Towers in Dhaka, Bangladesh: A Pilot Study. (20th August 2014) - Shariful Islam, Sheikh Mohammed
Abstract : Background . Over the last few years there have been concerns regarding the health effects of electromagnetic waves (EMW) produced by mobile phone base transmitter stations (BTS). Data on possible health effects of EMW in developing countries are rare. This study was conducted to determine the awareness and self-reported health hazards of EMW from the mobile phone BTS in Dhaka city. Methods . A cross-sectional study was conducted among 220 respondents living around BTS in Dhaka city. Data was collected on sociodemographic characteristics, mobile phone use, BTS and EMW awareness, and self-reported health problems. Results . The majority of respondents (92.7%) reported to have seen a BTS but only 29.5% knows how it works and 74.5% had no knowledge about the EMW. 49% respondents experienced sleeping disturbances while recent episodes of headache or dizziness were reported by 47% and mood change or anxiety or depression by 41%. About 22% complained about other physical or mental symptoms. Conclusion . Awareness about the possible health hazards from EMW of BTS is low among the inhabitants of Dhaka city. A number of respondents mentioned recent health effects but the association with BTS could not be established.